The conceptual model of the 4 dimensions to solve problems - Acevedo Borrego, Adolfo Oswaldo (2010)
There are two ways to solve problems in organizations. The fi rst is the traditional one, which states that unwanted situations are resolved by identifying the troubling facts and applying the appropriate technical tools, the second approach considers the resolution of problems is preset by the manager based on their perspective and infl uenced by the circumstances surrounding it. This paper is based on the second side, the manager knows business models and paradigms are learned through actual experience, theoretical study, technological design or creative intuition, which provide a particular perspective on the problem, which is complemented with relativism of circumstances: 1°) the role and status by level of resolution, 2°) professional and choice preferences, 3°) goals, group identity and culture, 4°) historical path and epistemological framework. The study will allow managers to identify their holistic conception of the world projected on the world of business. It provides criteria for identifying bias in problem solving and decision making.